Variability of Aldosterone Measurements During Adrenal Venous Sampling for Primary Aldosteronism. (12th November 2020) - Yozamp, Nicholas; Hundemer, Gregory L; Moussa, Marwan; Underhill, Johnathan; Fudim, Tali; Sacks, Barry; Vaidya, Anand
Abstract: BACKGROUND: Variability of aldosterone concentrations has been described in patients with primary aldosteronism. METHODS: We performed a retrospective cohort study of 340 patients with primary aldosteronism who underwent adrenal venous sampling (AVS) at a tertiary referral center, 116 of whom also had a peripheral venous aldosterone measured hours before the procedure. AVS was performed by the same interventional radiologist using bilateral, simultaneous sampling, under unstimulated and then stimulated conditions, and each sample was obtained in triplicate. Main outcome measures were: (i) change in day of AVS venous aldosterone from pre-AVS to intra-AVS and (ii) variability of triplicate adrenal venous aldosterone concentrations during AVS. RESULTS: Within an average duration of 131 minutes, 81% of patients had a decline in circulating aldosterone concentrations (relative decrease of 51% and median decrease of 7.0 ng/dl). More than a quarter (26%) of all patients had an inferior vena cava aldosterone of ≤5 ng/dl at AVS initiation. The mean coefficient of variation of triplicate adrenal aldosterone concentrations was 30% and 39%, in the left and right veins, respectively (corresponding to a percentage difference of 57% and 73%), resulting in lateralization discordance in up to 17% of patients if the lateralization index were calculated using only one unstimulated aldosterone-to-cortisol ratio rather than the average of triplicate measures. CONCLUSIONS: Circulating aldosterone levels can reach nadirs conventionally considered incompatible with the primary aldosteronism diagnosis, and adrenal venous aldosterone concentrations exhibit acute variability that can confound AVS interpretation. A single venous aldosterone measurement lacks precision and reproducibility in primary aldosteronism. Graphical Abstract: